How to reduce erroneous Emergency Department admissions for the frail elderly - Guarducci, G.; Lorenzini, C.; Ciacci, D.; Righi, L.; Pastorelli, M.; Nante, N. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. Readmission after a first hospitalization is a common occurrence. It may be due to incomplete treatment, poor care for underlying problems or reflect bad coordination with health services at the time of discharge. The aim of this study was to identify the factors and classify the pathologies that expose elderly patients to erroneous access to the Emergency/Urgency Department (EUD).Study design. Retrospective observational study.Materials and methods. From January 2016 to December 2019 we studied patients who had at least one readmission to the EUD in the six months following discharge. All EUD accesses of the same patient that occurred for the problem treated during the previous hospitalization were identified. Data was provided by the University Hospital of Siena. Patients were stratified by age, gender, and municipality of residence. We used an ICD-9-CM coding system to describe health problems. Statistical analysis was carried out with Stata software.Results. We studied 1,230 patients (46.6% females) the mean age was 78.2 ± 14.3. Most of them, 721 (58.6%) were ≥80 years old, 334 (27.1%) were 65-79, 138 (11.2%) were 41-64, and only 37 (3.0%) were ≤40. Patients who lived in Municipality of Siena had a lower probability to return than to those living in other municipalities (OR 0.76; 95%CI: 0.62-0.93; p